Addicted to love? Validity evidence for the Love Addiction Inventory — Brazilian version - Daniela Zibenberg; Jean Carlos Natividade (Psicologia: Reflexão e Crítica)
Abstract Background The Love Addiction Inventory (LAI) is an instrument developed to assess the six dimensions of addiction to a romantic partner: salience, tolerance, mood modification, relapse, withdrawal, and conflict. Objective The present study sought to adapt and provide validity evidence for the Brazilian version of the LAI. Method An online questionnaire was completed by 1310 Brazilian adults who were in romantic relationships. Results The data shows adequate reliability indices, validity evidence regarding the instrument’s internal structure, and validity based on the relationships among the variables. Notably, positive correlations between the LAI and Emotional Dependence Questionnaire and other addiction markers and negative correlations between the LAI and self-esteem were identified. Conclusion These findings provide a helpful instrument for symptom tracking and investigating interventions for the treatment of love addiction in future research.